2020
DOI: 10.1208/s12249-019-1611-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Thiolated Chitosan Microneedle Patch for Transdermal Delivery of Tacrolimus

Abstract: Microneedle patch is a prominent strategy with minimal invasion and painless application to improve skin penetration of drug molecules. Herein, we report microneedle patch (MNP) as an alternative to the oral route for the systemic delivery of tacrolimus (TM), an immunosuppressant drug. Thiolated chitosan (TCS) based microneedle patch was fabricated and characterized in vitro and in vivo for its mechanical strength, skin penetration, drug release, and skin irritation. The MNP having 225 needles with 575 μm show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Chemotherapy is one of the most important arsenals to kill tumors [69] . Various versatile carriers greatly improve the anti-tumor effect of chemotherapy drugs [ 70 , 71 ].For chemotherapy, MN@SRS have been employed for delivery of doxorubicin (Dox), dacarbazine, and other drugs for chemotherapy [72] , [73] , [74] . Typically, Kim et al reported a design of a biodegradable MN patch based on porous silicon ( p -Si) with a novel water-soluble backing ( Fig.…”
Section: The Biomedical Application Of Mn@srsmentioning
confidence: 99%
“…Chemotherapy is one of the most important arsenals to kill tumors [69] . Various versatile carriers greatly improve the anti-tumor effect of chemotherapy drugs [ 70 , 71 ].For chemotherapy, MN@SRS have been employed for delivery of doxorubicin (Dox), dacarbazine, and other drugs for chemotherapy [72] , [73] , [74] . Typically, Kim et al reported a design of a biodegradable MN patch based on porous silicon ( p -Si) with a novel water-soluble backing ( Fig.…”
Section: The Biomedical Application Of Mn@srsmentioning
confidence: 99%
“…Nevertheless, the microneedles were able to penetrate the tumor-mimicking agarose gel and promote layerbased drug release [129]. It is reported that the addition of the thiol group improves the mechanical properties of chitosan, and hence, thiolated MNs are prepared with optimum mechanical strength and sharpness [130].…”
Section: Chitin and Chitosan(cs)-based Mnsmentioning
confidence: 99%
“…In 2020, Ahmad et al fabricated thiolated chitosan (TCS)-based MN patch containing tacrolimus (TM), an immunosuppressant agent for the treatment of autoimmune disorders, by a mold casting method. The TCS-based MN patch was able to improve the drug bioavailability through circumvention of the hepatic first-pass metabolism and intestinal P-gp efflux and deliver the drug in a more sustained manner than oral administration [136]. Attenuated total reflectance-Fourier transform infrared (ATR-FTIR) analysis demonstrated that characteristic peaks of TM were retained in MN patches, suggesting the stability of TM during the preparation process of the patches.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%